Joyful Education Berbasis Nilai Spiritual Religius di SD NU Galur Kulon Progo, Yogyakarta - Muhammad Wahib Jamil (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aimed to explore fun educational programs in schools. This study used a phenomenological approach carried out at SD NU Galur Kulon Progo in Yogyakarta. Data was collected through interviews, observations, and in-depth discussions. The implementation of fun education at SD NU Galur is inseparable from the role of various stakeholders, the commitment of school residents, having the same direction and internalized in various school programs. Fun education programs at SD NU Galur Kulon Progo DI Yogyakarta can be a trendsetter for other schools to realize fun education. Fun education cannot be realized without the support of all components of education. For this reason, program synergy with various parties is imperative.